Reduced Time and Toxicity with SIB IMRT in Carcinoma Breast - Agrawal, Rashi; Agrawal, Sandeep; De, Sudarsan (International Journal of Applied Sciences and Biotechnology, 2015)
Introduction: To reduce treatment duration, we are treating our carcinoma breast patients with simultaneous integrated boost radiotherapy after breast conservation surgery. Here we are presenting our experience at median follow up of three years. Material and methods: Patients having at least 6 months of follow up after completion of radiotherapy were evaluated .All patients were treated with intensity modulated image guided radiotherapy technique. Dose prescribed to clinical target volume breast was 50 Gy in 25 fractions and CTV boost was 60 Gy in 25 fractions. Results: Median age of our patients was 49 years. Five patients (10.2%) had acute grade 2 skin toxicity and all other (89.7%) grade 1.Grade 2 toxicity was noted in patients with pendulous and bulky breast. Average treatment duration was 34 days (range 32-56 days). Median follow up is three years after completion of radiotherapy. Twenty six (53.06 %) patients had late grade zero and twenty three (46.9% ) grade 1 skin reactions. Conclusion: With simultaneous integrated boost in carcinoma breast patients, overall treatment time can be reduced without increasing early and late toxicities. Implementation is easy with decreased replanning workload. Henceforth SIB can be a feasible option for early breast cancer patients. Int J Appl Sci Biotechnol, Vol 3(3): 561-565